2009
DOI: 10.1007/s00769-009-0491-1
|View full text |Cite|
|
Sign up to set email alerts
|

International comparison of the determination of cadmium and lead in herb: the Comité Consultatif pour la Quantité de Matière (CCQM) pilot study CCQM-P97

Abstract: A Comite ´Consultatif pour la Quantite ´de Matie `re (CCQM) inter-laboratory comparison program, CCQM-P97, for the analysis of cadmium and lead in Herba Demodii Styracifolii was organized by the Hong Kong Government Laboratory. The objective of the program was to establish comparability of trace metals analysis in herbal matrices amongst the participating national metrology institutes. The arithmetic mean values of the 13 participants were 0.3186 mg kg -1 (RSD = 11.3%) and 1.650 mg kg -1 (RSD = 11.0%) for cadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Analysis of the same elements in Herba demodii styracifolii was the object of an inter-laboratory comparison organized under the aegis of the CCQM (Comit e Consultatif pour la Quantit e de Mati ere). 173 The arithmetic mean values of the 13 participating national metrology institutes were 0.3186 mg kg À1 (11.3% RSD) and 1.650 mg kg À1 (11.0% RSD) for Cd and Pb, respectively. Similar mean values were obtained by participants using double-IDMS techniques as well as by those using other techniques, although the former was recommended as it gives better precision.…”
Section: Applications: Drugs and Pharmaceuticals Traditional Medicine...mentioning
confidence: 94%
“…Analysis of the same elements in Herba demodii styracifolii was the object of an inter-laboratory comparison organized under the aegis of the CCQM (Comit e Consultatif pour la Quantit e de Mati ere). 173 The arithmetic mean values of the 13 participating national metrology institutes were 0.3186 mg kg À1 (11.3% RSD) and 1.650 mg kg À1 (11.0% RSD) for Cd and Pb, respectively. Similar mean values were obtained by participants using double-IDMS techniques as well as by those using other techniques, although the former was recommended as it gives better precision.…”
Section: Applications: Drugs and Pharmaceuticals Traditional Medicine...mentioning
confidence: 94%
“…Inter-laboratory comparison exercises have focused on the measurement of total Hg in soils, sediments and fish tissue, 261 total PTE in soils, 262 Cd and Pb in the medicinal plant Herba Desmodii Styracifolii 263 and Cr VI in soil, 259 the latter in association with the creation of the CRM described in the previous paragraph. Yip et al 264 have reviewed international intercomparisons conducted under the auspices of the Comit e Consultatif pour la Quantit e de Mati ere in the period 1998 to 2007.…”
Section: Analytical Quality Controlmentioning
confidence: 99%
“…The method adopted by HSA for Ca analysis was standard addition by multipoint calibration (Harris, 2003) using ICP-OES, which was shown to achieve good precision and accuracy in the international comparison (CCQM-K89). Prior to CCQM-K89, a comparison (CCQM-P97) was initiated for Cd and Pb analysis in a traditional Chinese herb (Wong et al, 2009). It was shown that trace metal analysis in herbal matrices was not method-dependent but the use of the highest metrological IDMS approach gave a better precision than other routine calibration methods.…”
Section: Introductionmentioning
confidence: 99%